2021
DOI: 10.3389/fanim.2021.650347
|View full text |Cite
|
Sign up to set email alerts
|

The Influencing Factors of Bacterial Resistance Related to Livestock Farm: Sources and Mechanisms

Abstract: Bacterial resistance is a complex scientific issue. To manage this issue, we need to deeply understand the influencing factors and mechanisms. Based on the background of livestock husbandry, this paper reviews the factors that affect the acquisition of bacterial resistance. Meanwhile, the resistance mechanism is also discussed. “Survival of the fittest” is the result of genetic plasticity of bacterial pathogens, which brings about specific response, such as producing adaptive mutation, gaining genetic material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 118 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have demonstrated a link between the use of antibiotics in food-producing animals, especially for growth promotion, and AR in people who either live on or near farms [ 15 ]. Additionally, drug-resistant strains can emerge if the prescribed antibiotics are not changed in a timely manner [ 26 ]. These bacteria generally develop resistance to antibiotics through several different resistance mechanisms, including blocking the antibiotic’s target sites, altering the permeability of cell membranes, and producing antibiotic-inactivating enzymes [ 27 ].…”
Section: Antibiotic Resistance In Livestockmentioning
confidence: 99%
“…Numerous studies have demonstrated a link between the use of antibiotics in food-producing animals, especially for growth promotion, and AR in people who either live on or near farms [ 15 ]. Additionally, drug-resistant strains can emerge if the prescribed antibiotics are not changed in a timely manner [ 26 ]. These bacteria generally develop resistance to antibiotics through several different resistance mechanisms, including blocking the antibiotic’s target sites, altering the permeability of cell membranes, and producing antibiotic-inactivating enzymes [ 27 ].…”
Section: Antibiotic Resistance In Livestockmentioning
confidence: 99%
“…Airborne bacteria within and near farms carry more AR and virulence genes than those isolated from hospital air samples [ 256 ]. Arthropods carry AR bacteria from livestock units into surrounding areas [ 257 ] (a report from Germany shows that flies carrying bla CTX-M-1 and fluoroquinolone resistance genes from pig farms can be found 2 km away into urban areas [ 258 ]). Livestock production is a major source of AR genes in the soil [ 259 ].…”
Section: Non-canonical Dispersion Of Armentioning
confidence: 99%
“…Bacterial resistance refers to the ability of bacteria to withstand exposure to heavy metals, antimicrobial agents such as antibiotics, disinfectants, and antiseptics. This resistance can arise through a variety of mechanisms, including genetic mutations, horizontal gene transfer, and selective pressure from repeated exposure to such agents (Guo et al, 2021).…”
Section: Bacterial Resistance To Heavy Metalsmentioning
confidence: 99%